No Improvement in Hemoglobin A1c Following Hepatitis C Viral Clearance in Patients With and Without HIV. (17th November 2017) - Chaudhury, Chloe S; Sheehan, Julia; Chairez, Cheryl; Akoth, Elizabeth; Gross, Chloe; Silk, Rachel; Kattakuzhy, Sarah; Rosenthal, Elana; Kottilil, Shyam; Masur, Henry; Hadigan, Colleen
Abstract : In a relatively large cohort of DAA-treated hepatitis C patients followed for a median 28 months, no improvements in hemoglobin A1c or glucose followed clearance of the virus. These results remained consistent regardless of HIV status, diabetes, or fibrosis stage. Abstract: Hepatitis C clearance with directly acting antivirals (DAAs) may be associated with acute decreases in hemoglobin A1c (HbA1c). We prospectively evaluated 251 chronic hepatitis C virus (HCV)-infected subjects (31% human immunodeficiency virus [HIV] positive) pre- and post-DAA therapy (median follow-up 28 months). Changes in HbA1c and glucose were minimal and did not differ by sustained virologic response (SVR), HIV, diabetes, or fibrosis. Following SVR, mean change in HbA1c was −0.022 ± 0.53%; however, total and low-density lipoprotein cholesterol increased significantly. Subjects with HIV had smaller transaminase reductions after SVR. Sustained benefits in glycemia were not identified following HCV clearance irrespective of HIV, diabetes, or fibrosis stage, whereas lipid alterations may warrant further investigation.